RETRACTED: THE RESPONSIBILITY OF A PRINCE IN ANCIENT RUSSIA: PAGAN AND CHRISTIAN - Igor Lisyuchenko (Гуманитарные и юридические исследования)
RETRACTED ARTICLEThe article examines the responsibility of the ruler for the dysfunctional state of affairs in the country. A careful study of the biblical evidence shows that it is the legacy of the pagan past.